Pengaruh Pendekatan Pendidikan Mate matika Realistik Indonesia (PMRI) Terhadap Hasil Belajar Penyajian Data di Kelas V Sekolah Dasar - Syifa Elhusna; syafri ahmad (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2022)
This study aims to determine the effect of student learning outcomes on learning mathematics for data presentation material in class V of Elementary School for the 2019/2020 academic year. The population in this study were all elementary schools in the Cluster II of Lubuk Kilangan District, which consisted of 7 schools (3 schools were groups). The samples of this research were class V SDN 08 Padang Besi, totaling 28 people as the experimental class, and class V SDN 06 Padang Besi, totaling 30 people as the control class. The instrument used in this study was an objective test in the form of multiple choices. The data analysis technique used was the t-test. The results showed that the average score for the experimental class that applied learning with the Indonesian Realistic Mathematics Education (PMRI) approach was 86.7 higher than the average value for the control class that applied conventional learning was 73.2. This proves that there is a significant influence on student learning outcomes in mathematics learning in elementary schools using the Indonesian Realistic Mathematics Education approach.